1989
DOI: 10.1302/0301-620x.71b1.2915016
|View full text |Cite
|
Sign up to set email alerts
|

The axis of rotation of the ankle joint

Abstract: The axis of the talo-crural joint was analysed by roentgen stereophotogrammetry in eight healthy volunteers. Examinations were performed at 10#{176} increments offlexion and pronation/supination of the foot as well as medial and lateral rotation of the leg. Results indicate that the talo-crural joint axis changes MD, Lecturer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(137 citation statements)
references
References 7 publications
12
123
2
Order By: Relevance
“…Kinematics of the ankle complex has been studied in the past [10,11] and while some models describe its motion as purely rotational [12][13][14][15], others consider foot motions to be a consequence of rotations about two hinge/revolute joints (biaxial) in series [16,17] [ [18][19][20][21][22][23][24]. Ankle complex kinematics have also been modelled using four-bar linkages and spatial parallel mechanisms [15,25].…”
Section: Accepted Manuscript > Replace This Line Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Kinematics of the ankle complex has been studied in the past [10,11] and while some models describe its motion as purely rotational [12][13][14][15], others consider foot motions to be a consequence of rotations about two hinge/revolute joints (biaxial) in series [16,17] [ [18][19][20][21][22][23][24]. Ankle complex kinematics have also been modelled using four-bar linkages and spatial parallel mechanisms [15,25].…”
Section: Accepted Manuscript > Replace This Line Withmentioning
confidence: 99%
“…(8) (9) (10) (11) Here is the deflection along single spring, whereas is the effective elongation produced in the spring-dashpot unit. The dashpot is assumed to be having a linear elongation ( ) with as its damping coefficient.…”
Section: B Characterization Of Musculoskeletal Elements Of the Anklementioning
confidence: 99%
See 1 more Smart Citation
“…Some individuals have fairly vertical calcanei during stance in the presence of midfoot pronation. Lundberg et al 13 found that during foot pronation, the largest amount of motion occurred in the talonavicular joint, followed by the talocalcaneal joint. The correlation between relaxed rearfoot angle and navicular drop in the entire group of subjects was r = 0.43 (P = .002), where 19% of the variance could be explained between the 2 variables.…”
Section: 810mentioning
confidence: 99%
“…The axis of rotation of the ankle, assumed to cross the tip of the malleoli in the neutral dorsiflexion/ plantar flexion joint position, 28 was aligned as closely as NS [8] PS [8] NS [8] PS [8] NS [8] possible with the axis of rotation of the torque recorder. Then, subjects were asked to perform five maximal voluntary isometric contractions of 5 s duration in plantar flexion and dorsiflexion and bilaterally.…”
Section: Torque Measurementmentioning
confidence: 99%